Morphology of a Hidden Tube: Resin Injection and CT Scanning Reveal the Three‐dimensional Structure of the Spiracle in the Japanese Bullhead Shark Heterodontus japonicus (Chondrichthyes; Heterodontiformes; Heterodontidae). Issue 8 (7th May 2018) - Tomita, Taketeru; Toda, Minoru; Miyamoto, Kei; Ueda, Keiichi; Nakaya, Kazuhiro
ABSTRACT: The spiracle of elasmobranchs (sharks, skates, and rays) is a gill‐slit‐derived tube located behind the eye. Its inner structure was well studied in the late nineteenth to early twentieth century, but its entire morphology has rarely been characterized and is poorly understood. The present study shows the three‐dimensional morphology of the spiracular tube for the first time, using resin injection and CT scanning, in the Japanese bullhead shark. The spiracular tube is characterized by the presence of two caeca (dorsal and ventral spiracular caeca) on the medial wall of the spiracular tube and the presence of a pseudobranch on the anterior wall. This study provides a basis for further studies on the morphological diversity, function, and evolution of spiracles in elasmobranch fishes. Anat Rec, 2018. © 2018 Wiley Periodicals, Inc.